2001
DOI: 10.3346/jkms.2001.16.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Deflazacort Increases Osteoclast Formation in Mouse Bone Marrow Culture and the Ratio ofRANKL/OPGmRNA Expression in Marrow Stromal Cells

Abstract: Information on precise effects of deflazacort on bone cell function, especially osteoclasts, is quite limited. Therefore, the present study was undertaken to test effects of deflazacort on osteoclast-like cell formation in mouse bone marrow cultures and on the regulation of osteoprotegerin (OPG) and its ligand (RANKL) mRNA expressions by RT-PCR in the ST2 marrow stromal cells. TRAP-positive mononuclear cells increased after the treatment of deflazacort at 10(-9) to 10(-7) M alone for 6 days in a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Either in a cell membrane-bound or in a soluble form, RANKL, receptor activator of NF-kappa β (RANK), stimulates osteoclastogenesis and osteoclastic bone resorption. Factors that stimulate bone resorption increase RANKL expression and, with some exceptions, decrease OPG expression [69]. In the present study, animals of HFD-fed group showed a significant decrease in serum level of OPG (Figure 3(b)) and a significant increase in serum level of RANKL (Figure 3(a)), compared to control group of rats.…”
Section: Discussionsupporting
confidence: 56%
“…Either in a cell membrane-bound or in a soluble form, RANKL, receptor activator of NF-kappa β (RANK), stimulates osteoclastogenesis and osteoclastic bone resorption. Factors that stimulate bone resorption increase RANKL expression and, with some exceptions, decrease OPG expression [69]. In the present study, animals of HFD-fed group showed a significant decrease in serum level of OPG (Figure 3(b)) and a significant increase in serum level of RANKL (Figure 3(a)), compared to control group of rats.…”
Section: Discussionsupporting
confidence: 56%
“…18,23 Experimental studies suggest that deflazacort may have bone-sparing effects via its effects on bone formation in comparison with dexamethasone or cortisol. [24][25][26] Deflazacort and dexamethasone have similar effects on stimulating osteoclast formation. 26 Evidence of the relative bone sparing in children is based on reports in nephrotic syndrome and rheumatologic conditions where nonsignificant differences in densitometry results were reported.…”
Section: Daily Deflazacort Daily Prednisolone Intermittent Deflazacor...mentioning
confidence: 99%
“…[24][25][26] Deflazacort and dexamethasone have similar effects on stimulating osteoclast formation. 26 Evidence of the relative bone sparing in children is based on reports in nephrotic syndrome and rheumatologic conditions where nonsignificant differences in densitometry results were reported. [27][28][29] Owing to its improved tolerability, deflazacort is often maintained at higher doses.…”
Section: Daily Deflazacort Daily Prednisolone Intermittent Deflazacor...mentioning
confidence: 99%
“…RANKL and osteoprotegerin (OPG) are cytokines related to osteoclast formation, and the RANKL:OPG ratio is frequently used as a measure to indicate whether a system has the potential to generate osteoclasts [ 19 ]. When this ratio is favorable to osteoclastogenesis, the RANK–RANKL interaction will lead to differentiation of the osteoclast precursor into osteoclasts [ 20 ]. In RANKL-deficient mice, the effect of transgenically induced RANKL expression by T and B cells normalizes osteoclast formation in long bones but not in the jaw.…”
mentioning
confidence: 99%